“Immunizing” communities: social media and preventing/countering violent extremism initiatives by former terrorists - Widjanarko, Putut; Chusjairi, Juni Alfiah; Sunaryo (Frontiers in Communication, 2025)
This study explores the case of a reformed former terrorist convict who, through self-initiated efforts, established media-based Preventing/Countering Violent Extremism (P/CVE) initiatives utilizing his YouTube channel. Amidst the ongoing contest within the online public media sphere to counter harmful extremist content, the voices of credible individuals become paramount. This research investigates how Sofyan Tsauri adopted and utilized social media to contribute to P/CVE efforts and engage in civic participation. Consequently, this study employs the Unified Theory of Acceptance and Use of Technology (UTAUT), a socio-technical approach underutilized in media-based P/CVE research. While UTAUT studies are predominantly quantitative, this research adopts a qualitative approach to gain deeper insights, employing a single intrinsic case study design focused on Sofyan Tsauri, whose unique experiences and actions are particularly suited to addressing the research question. Data collection was conducted through semi-structured, in-depth interviews and document analysis. Interview transcripts were analyzed using Nvivo software, employing deductive coding based on UTAUT dimensions. The findings confirm that performance expectancy, effort expectancy, and social influence are associated with the motivation to adopt YouTube, with performance expectancy as the dominant driver. However, this research reveals crucial deviations from the original UTAUT framework. Firstly, this study demonstrates that the former convict’s past experience with digital media enhances his performance expectancy. This diverges from the UTAUT model, which posits that prior experience would enhance effort expectancy, social influence, and facilitating conditions. Secondly, this research also identifies a novel dimension, the “restorative motive,” an intrinsic drive within the former convict to atone for past transgressions by engaging ardently to counter and provide alternative narratives to harmful and extremist content, including online. Therefore, these findings offer more nuanced insights into adopting individual-level digital media technology, enriching the theoretical discourse beyond traditional UTAUT applications. By acknowledging the restorative motives in supporting former extremists’ use of social media for P/CVE, governments, and civil society, organizations can enhance these individuals’ capacity to provide alternative and counter-narratives to mitigate online radicalization. This study suggests avenues for future research to deepen our understanding of digital communication practices in fostering a safer and more peaceful world.